2003
DOI: 10.1046/j.1344-3941.2003.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Biceps femoris and Longissimus thoracis muscles of five cattle breeds grown in a feedlot system

Abstract: Our experiment was conducted to study physical quality and chemical composition of meat of Angus (A), Hereford (H), Friesian Holstein (FH), Australian Commercial Cross (ACC) and Murray Grey (MG) cattle breeds grown in a feedlot system. Significant differences were observed among five cattle breeds for cooking loss, tenderness, fatty acid composition, collagen and cholesterol content of meat. However, pH, water‐holding capacity, water, ash, fat and crude protein contents were not different. Cholesterol content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
4

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
8
1
4
Order By: Relevance
“…This observation confirms that of Carnovale and Nicoli (2000) who concluded that Italian meat showed a favourable intramuscular fatty acid composition with high PUFA content. Muscle with a high percentage of unsaturated fatty acids (UFA) generally scored higher in taste panel evaluation (Westerling and Hedrick, 1979) and food with high UFA, especially PUFA, is good for human health (Rusman et al, 2003). The ω-6/ω-3 ratio was higher than the value (less than 3) reported by Scollan et al (2006) but lower than that registered by Warren et al (2003) for steers fed corn silage and concentrates (8.9).…”
Section: Samples Of Longissimus Thoracis (Lt) Semitendinosus (St) Icontrasting
confidence: 39%
See 1 more Smart Citation
“…This observation confirms that of Carnovale and Nicoli (2000) who concluded that Italian meat showed a favourable intramuscular fatty acid composition with high PUFA content. Muscle with a high percentage of unsaturated fatty acids (UFA) generally scored higher in taste panel evaluation (Westerling and Hedrick, 1979) and food with high UFA, especially PUFA, is good for human health (Rusman et al, 2003). The ω-6/ω-3 ratio was higher than the value (less than 3) reported by Scollan et al (2006) but lower than that registered by Warren et al (2003) for steers fed corn silage and concentrates (8.9).…”
Section: Samples Of Longissimus Thoracis (Lt) Semitendinosus (St) Icontrasting
confidence: 39%
“…Considering the differences among the muscles, cholesterol values were significantly (P<0.05) lower for IP. Cifuni et al (2004) found no differences in cholesterol contents among muscles, while Rusman et al (2003) found significant differences. This contradiction is probably due to the different muscles analysed in each experiment.…”
Section: Samples Of Longissimus Thoracis (Lt) Semitendinosus (St) Imentioning
confidence: 76%
“…Several authors reported that the type of muscle significantly influenced the intramuscular lipid content (Talpur et al, 2008;Marichal et al, 2003), although the sign of the differences may vary with age (Mahgoub et al, 2002) and genotype (Santos et al, 2007;Velasco et al, 2004;Barton et al, 2008). Rusman et al (2003) explained the lower fat content in biceps femoris muscle compared to LT due to its higher activity.…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini disebabkan oleh kandungan lemak intramuskular pada sapi jantan lebih sedikit dibandingkan sapi betina,rendahnya lemak intramuskuler tersebut menyebabkan kadar air di dalam daging menjadi lebih tinggi. Rusman et al (2003) menyebutkan bahwa adanya perbedaan kadar air daging dapat dipengaruhi oleh lemak intramuscular, bila kadar air daging meningkat maka kadar lemak akan menurun.…”
Section: Komposisis Kimia Dagingunclassified
“…Sapi yang dilakukan pengujian adalah sapi yang berumur 2,5 tahun pada jenis kelamin jantan. Rusman et al (2003) menyatakan bahwa kandungan kolesterol daging di antara daging sapi dapat berbeda yang dipengaruhi oleh bangsa ternak, umur ternak serta kandungan marbling. Rhee et al (1982) menyataan bahwa otot yang memiliki marbling lebih banyak mempunyai kandungan kolesterol yang lebih tinggi pula.…”
Section: Komposisis Kimia Dagingunclassified